Strategi Bersaing Antar Pedagang Kuliner Taman Sangomang Palangka Raya - Jusmiyanti Jusmiyanti; Rinto Alexandro; Sundari Sundari; Sri Rohaetin; Hendrowanto Nibel; Susan Daniel; Nonsihai Nonsihai; Susi Sukarningsi (FKIP, Universitas Palangka Raya, 2022)
The problem raised in this research is how is the competitive strategy between culinary traders in the Sangomang Park, Palangka Raya. With the number of informants as many as 21 people and data collection techniques used in this study were documentation and interviews. The data analysis methods used are: (1) Data Reduction, (2) Data Presentation, and (3) Data Conclusion Drawing. The results of this study are culinary traders at Sangomang Park in terms of products using 3 competitive strategies that are applied, including developing existing products, making new products that do not exist in other traders, and maintaining or maintaining the quality of existing flavors. For the price applied, the trader follows or equals the price of the surrounding trader. Then in terms of service, culinary traders in Sangomang Park as a whole apply good service with smiles, greetings and greetings. Regarding promotion, there are those who promote their wares through social media and some only through their families, employees, and people they know. Even so, the income of traders during the pandemic decreased drastically, in this situation, traders rely on online motorcycle taxi services that accept delivery services for buyers, even though some continue to sell and some are closed by making independent businesses in their respective homes.